The Contributions of Abd al-Mu'min ibn Ali al-Kumi al-Jaza'iri to the Religious Unity of the Islamic West - Ashi, ALI (Tobruk University Journal of Social and Human Sciences, 2025)
Abd al-Mumin ruled thirty-four years, one of the most prosperous times of Morocco, and he inherited from Ibn Tumart a rebellious movement that transformed it into a state, and set for it the administrative rules and systems that enable the state to run the affairs of the state and manage its affairs, thus contributing to the emergence of a civilized interaction between the countries of the Maghreb and Andalus at all levels .The following problem: How was Abd al-Mumin bin Ali Talib al-Asimah al-Simple, able to establish the largest country in the Islamic West?Objectives of the topic:- Show Abdulmomen's contribution to the unity of the countries of the Maghreb, especially the religious ones.In this intervention, we will follow the narrative historical approach in addition to the descriptive synthesis approach, through our description of the personality of Abd al-Mumin, his environment, the circumstances of his formation, and his most important achievements.To answer the previous problem and the rest of the questions, the intervention should be divided into several elements:an introductionAbdul Mu'min birth and lineageAbd al-Mumin was influenced by the thought of al-Mahdi ibn TumartEstablishment of the state and unification of the Islamic MaghrebReligious and cultural unity of Morocco during the era of Abdel-MuminConclusion.